The Order of Concurrent Training Does not Affect Soccer-Related Performance Adaptations - McGawley, K.; Andersson, P.-I. (International Journal of Sports Medicine, 2013)
Despite the wealth of evidence regarding physical training strategies in soccer, there is little information regarding soccer-specific concurrent training and the effects of training order. The current study aimed to: i) quantify the effects of concurrent high-intensity run-based training (HIT) and strength- and power-based training (STR) on soccer-specific performance, and ii) investigate the order effect of completing HIT and STR either first or second within training sessions. Eighteen semi- and fully-professional players completed a battery of field- and gym-based tests before and after a 5-week pre-season training intervention. Players were pair-matched and completed 3 sessions per week of HIT followed by STR (n=9) or STR followed by HIT (n=9). ANCOVA tests revealed no differences between groups for changes in any of the measures (p>0.05). However, a training effect was observed for all measures (p<0.05), with 10-m sprint, 6×30-m repeated sprint, 40-m agility and Yo-Yo test performances improving by 1.8±2.6%, 1.3±1.8%, 1.0±1.5% and 19.4±23.4%, respectively (n=18). In conclusion, there was a positive effect of the concurrent training approach on key measures of soccer performance, but the order of completing HIT and STR appears inconsequential to performance adaptations.
Keywords: pre-season; high-intensity; strength; power; session organisation